THE DEVELOPMENT OF SCIENCE TEACHING MATERIALS INTEGRATED ETHNOSCIENCE WITH WEBBED TYPE ON ADDITIVE AND ADDICTIVE TOPIC - Tania Mutiara rizki; Rahmah Evita Putri (Universe, 2022)
On teaching and learning process, educators are required to be able to create situations that allow students to be active and creative. One of the efforts to integrate science with ethnoscience in the form of teaching materials is one of the breakthroughs in the development of teaching materials. The observation in SMPN 11 Padang shows that still used teaching materials in the form of LKPD which colorless and newspaper base paper. This made students' interest in learning are decline. Based on the observation result, the researcher wants to do research that the aim is to produce science teaching material integrated ethnoscience that valid and practical to use. The type of research used is Research and Development (R&D). The research method used in the 3 stages of the 4-D (Four-D model), namely defines, design, and development. Teaching materials are valid when the eligibility criteria for content, language, presentation, and graphics are reached by the validator's expert. Teaching materials are practical when the criteria for ease of use, time efficiency, and benefits have been assessed by teachers and students. The validity and practicality values obtained through instruments in the form of interview sheets, validity questionnaires, and practicality questionnaires. The results showed that the integrated ethnoscience science teaching materials can be used with valid and practical categories. © Department of Science Education, Universitas Negeri Padang Keywords: Science Teaching Materials, Webbed, Ethnoscience, 4-D Model.